One iguana, two iguanas : a story of accident, natural selection, and evolution - Collard, Sneed B. (How nature works., 2018)
Examines the peculiar iguana species of the Galápagos Islands that swims and dives underwater to eat. Tracks the evolutionary changes that led to this particular species of iguana and the work of Charles Darwin that led to this discovery. Includes a glossary, resources for further information, diagrams, a map, and color photographs.